A facile mechanochemical route to a covalently bonded graphitic carbon nitride (g-C3N4) and fullerene hybrid toward enhanced visible light photocatalytic hydrogen production. Issue 17 (19th April 2017) - Chen, Xiang; Chen, Huanlin; Guan, Jian; Zhen, Jieming; Sun, Zijun; Du, Pingwu; Lu, Yalin; Yang, Shangfeng
Abstract : Covalently bonded g-C3 N4 and fullerene were synthesized by ball-milling, showing a H2 production rate of 266 μmol h −1 g −1 under visible light, which is about 4.0 times higher than with pristine g-C3 N4 . Abstract : Graphitic carbon nitride (g-C3 N4 ) as an emerging two-dimensional (2D) nanomaterial has been commonly used as a metal-free photocatalyst with potential applications in visible light photocatalytic water-splitting. However, the photocatalytic activity of g-C3 N4 is quite low due to its relatively large band gap and the existence of contact resistance between the nanosheets. Herein we report for the first time the facile synthesis of a covalently bonded g-C3 N4 /C60 hybrid via a solid-state mechanochemical route and its application in photocatalytic hydrogen production under visible light. The g-C3 N4 /C60 hybrid was synthesized by ball-milling g-C3 N4 and C60 in the presence of lithium hydroxide (LiOH) as a catalyst. The hybrid nature and conformation of the g-C3 N4 /C60 hybrid were confirmed by a series of spectroscopic and morphological studies, featuring the covalent bonding of C60 onto the edges of g-C3 N4 nanosheets via a four-membered ring of azetidine, which has never been reported in fullerene chemistry. The g-C3 N4 /C60 hybrid was further applied to metal-free visible light photocatalytic hydrogen production, affording a H2 production rate of 266 μmol h −1 g −1 without using any noble metal cocatalyst such as Pt, which is about 4.0 times higher than that obtained for the pristine g-C3 N4 photocatalyst.